Catalytic conversion of 1,2-dichloroethane over Ni-Pd system into filamentous carbon material - Bauman Yu. I. Yury; Shorstkaya Yu. V.; Mishakov I. V. Iljya Vladimirovich; Plyusnin P. E. Pavel Evgenjevich; Shubin Yu. V. Yury Viktorovich; Korneev D. V. Denis; Stoyanovskii V. O. Vladimir; Vedyagin A. A. Aleksey Anatolievich (2017, 2017)
Title screen